Left out, left behind. The people lost to Britain's workforce. - Willett, David MP; Hillman, Nicholas; Bogdanor, Adam (London, 2003)
"Over the past decade, there has been a sustained fall in the number of people who are unemployed. In the spring of 1992, there were around 2.8 million unemployed people in Britain. That figure is now down to 1.5 million. What is much less well known is that this drop in unemployment has been accompanied by a rise in the number of people who are neither employed nor officially unemployed – a group described as economically inactive. Over 7.7 million people of working age now count as economically inactive, up from 7.3 million in 1992 and 7.6 million in 1997.